Evaluación de la calidad de agua,utilizada en los sistemas de riego en el cultivo de banano, machala - el oro - Chacha Ochoa, Natali Silvana (Machala : Universidad Técnica de Machala, 2021)
Water is an essential vital liquid as much as for human beings, animals and plants, water today is used for agricultural purposes. In this study, water analysis was carried out from two different water sources, such as canal and well water, in order to assess the quality of water available for irrigation of banana crops in the Canton "Machala", using the main indicators to assess the quality of irrigation water. Water quality is a term used to describe the chemical and physical characteristics of water, it depends on the use that will be carried out, to obtain high quality crops it is necessary to know the optimal conditions and it also varies from the source of water that will be used. since each water contains different characteristics as well as well and canal water that differentiate them from one another. The water will be of good quality for agricultural irrigation use, fulfilling its basic functions for the growth of plants that guarantee optimal performance without causing harmful effects to the soil, the salt content may be the main reason for the deterioration of the quality of agricultural water. , the use of saline water for irrigation can reduce the absorption of water in plants, the EC indicates the total dissolved solids in the water and is the most important parameter to determine salinity hazards. The samples from the two water sources (channel and well) were randomly selected, these samples were taken from six different farms in the Machala canton and the concentration analysis of cations (Ca, Mg, K, Na), anions (NO3 , SO4, Cl, HCO3), Ph and electrical conductivity, to obtain reliable results the water samples were chosen to be sent to the NEMALAB laboratory that has the respective certification and accreditation in the city of Machala. The corresponding water quality indicator calculations to assess its quality are the following parameters such as: He calculated the sodium absorption ratio index (RAS), effective salinity (SE), potential salinity (SP) and residual sodium carbonate ( CSR) was allowed to be achieved through the respective established formulas to reach the expected results. The RAS values can be tolerated if the salinity of the irrigation water increases, on the contrary if the RAS of the water decreases it can be dangerous in the soil if the EC is low. Resulting in a low content of cations and anions in well water has a difference with channel water, a statistical analysis determines the differences in the physical-chemical parameters of the two sources of well and channel water, determining the descriptive parameters. , Shapiro Wills test and correlation. Allowing to know the conditions in which the water that is used for irrigation in the banana crop is found and to reveal the adequate water for the use of irrigation, in order to obtain a better yield and development in the crop.
El agua es un líquido vital indispensable tanto como para los seres humanos , animales y las plantas, el agua hoy en día es utilizada con fines agrícolas. En este estudio se realizó análisis de agua de dos diferentes fuentes de agua como es el agua de canal y pozo, con la finalidad de evaluar la calidad de agua disponibles para el riego del cultivo de banano en el Cantón “ Machala” , usando los principales indicadores para evaluar la calidad del agua de riego. La calidad de agua es un término usado para describir las características químicas y física del agua, depende del uso que se llevará a cabo, para obtener cultivos de alta calidad es necesario conocer las condiciones óptimas y también varía de la fuente de agua que será utilizada ya que cada agua contiene diferentes características tanto como el agua de pozo y canal que las diferencia de una con la otra. El agua será de buena calidad para uso de riego agrícola cumpliendo con sus funciones básicas para el crecimiento de las plantas que garantizan rendimiento óptimas sin ocasionar efectos perjudiciales al suelo, el contenido de sales puede ser la principal razón del deterioro de la calidad del agua agrícola, el uso de agua salina para el riego puede reducir la absorción de agua en las plantas, la CE indica el total de sólidos disueltos que hay en el agua y es el parámetro más importante para determinar peligros de salinidad. Las muestras de las dos fuentes de agua (canal y pozo) se seleccionaron al azar estas muestras fueron tomadas de seis diferentes fincas del cantón Machala y se realizó el análisis de concentración de cationes (Ca,Mg,K,Na), aniones (NO3,SO4,Cl,HCO3), Ph y conductividad eléctrica, para obtener resultados confiables las muestras de agua se optó por ser enviadas al laboratorio NEMALAB que cuenta con las respectivas certificación y acreditación en la ciudad de Machala. Los correspondientes cálculos indicadores de la calidad del agua para evaluar su calidad son los siguientes parámetros como: El calculó el índice de relación de absorción de sodio (RAS), Salinidad efectiva (SE), Salinidad potencial (SP) y carbonato de sodio residual (CSR) se permitió conseguir mediante las respectivas fórmulas establecidas para llegar con los resultados esperados. Los valores del RAS se pueden tolerar si la salinidad del agua de riego aumenta, por el contrario si baja el RAS del agua puede ser peligrosa en el suelo si la CE es baja. Dando como resultado un bajo contenido de cationes y aniones en agua de pozo ha diferencia con el agua de canal, mediante un análisis estadístico se determina las diferencias de los parámetros físico-químico de las dos fuentes de agua pozo y canal, determinando los parámetros descriptivos, prueba de Shapiro Wills y correlación. Permitiendo conocer las condiciones en la que se encuentra el agua que son utilizadas para el riego en el cultivo de banano y dejar conocer el agua adecuada para el uso de riego, con la finalidad de obtener un mejor rendimiento y desarrollo en el cultivo.
Keywords: CALIDAD; AGUA; CORRELACIÓN; CONDUCTIVIDAD